2017
DOI: 10.1128/aac.00487-17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rifampin on the Single-Dose Pharmacokinetics of Oral Cabotegravir in Healthy Subjects

Abstract: Drug-drug interactions between antiretroviral medications and rifampin complicate the treatment of HIV and tuberculosis coinfection. This study evaluated the effect of rifampin on the pharmacokinetics of oral cabotegravir, an integrase strand transfer inhibitor being investigated for long-acting treatment and prevention of HIV-1 infection. This was a phase I, single-center, open-label, fixed-sequence crossover study in healthy adults. The objective was to evaluate the effect of steady-state rifampin on the sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…Chromaturia, reported in three subjects in group E (rifampin ? ozanimod), is a well-documented and benign side effect of rifampin [14,15]. S1P receptor modulators may cause a transient decrease in heart rate (HR) and AV conduction delays upon initiation of dosing [16].…”
Section: Discussionmentioning
confidence: 99%
“…Chromaturia, reported in three subjects in group E (rifampin ? ozanimod), is a well-documented and benign side effect of rifampin [14,15]. S1P receptor modulators may cause a transient decrease in heart rate (HR) and AV conduction delays upon initiation of dosing [16].…”
Section: Discussionmentioning
confidence: 99%
“…It can also be used with efavirenz without dose modifications and with raltegravir or dolutegravir, provided the integrase inhibitor dose is doubled to twice daily. Rifampicin reduces cabotegravir and bictegravir concentrations significantly, more work is needed to determine whether or not these DDI can be overcome with dose modifications [18]. Rifampicin and rifapentine reduce exposure to almost all known protease inhibitors and co-administration is not recommended, with the exception of lopinavir/ritonavir, where the use of double doses can be considered, with close monitoring, in settings where rifabutin is not available [19,20].…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…Cabotegravir had no significant effect on the pharmacokinetics (PK) of midazolam, a sensitive cytochrome P450 3A4 probe substrate, a levonorgestrel/ethinyl estradiol–containing oral contraceptive, or the nonnucleoside reverse‐transcriptase inhibitor rilpivirine . Rifampin significantly reduced cabotegravir exposures, therefore, potent enzyme inducers should not be coadministered with cabotegravir …”
mentioning
confidence: 99%
“…8,10,11 Rifampin significantly reduced cabotegravir exposures, therefore, potent enzyme inducers should not be coadministered with cabotegravir. 12 Single-dose oral cabotegravir 30 mg is readily absorbed with a median time to peak plasma concentration (t max ) of 2 hours and has a plasma apparent terminal-phase half-life (t 1/2 ) of approximately 38.5 hours under fasted conditions and an area under the concentration-time curve from time 0 to infinity (AUC 0-Ý ) of 146 ÎŒg‱h/mL. 12,13 Previous studies demonstrated that a moderate-fat meal (30% fat, ß670 calories) did not significantly affect the PK of cabotegravir administered at 10-and 30-mg doses, respectively, using early prototype formulations (Supplemental Data).…”
mentioning
confidence: 99%
See 1 more Smart Citation